EFEKTIVITAS METODE ANALISIS GLASS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KATA BAGI ANAK DISLEKSIA KELAS III SDN 09 KOTO LUAR PADANG - Ernawati - (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract:The background of this research is the difficulty in reading the words of a child vowels in SDN 09 Koto Luar Padang. Analisis Glass method is a method of teaching through code-breaking group of letters in words. The purpose ofthis study is to prove the effectiveness of the method of analysis glass in improving the ability to read the word vowels. This type of research is Single Subject Research with ABA design. The results showed Analisis Glass method is effective inimproving the ability to read words vowels dyslexia children in SDN 09 Class III Koto Luar Padang.